Proxmox-Based virtualization for CBT moodle hosting: VM vs LXC performance evaluation - Parulian, Parulian (Institute of Computer Science (IOCS), 2025)
Server virtualization plays a critical role in managing e-learning infrastructure, particularly in Computer-Based Testing (CBT) systems that require high performance, stability, and efficient resource utilization. Proxmox Virtual Environment (Proxmox VE) provides two commonly used virtualization models: Virtual Machines (VM), which rely on full virtualization, and Linux Containers (LXC), which utilize lightweight container-based virtualization. This study aims to evaluate and compare the performance of Moodle as a CBT platform when hosted on VM and LXC environments in Proxmox VE. The evaluation focuses on several performance indicators including CPU utilization, memory consumption, I/O throughput, response time, and system behavior under concurrent user load. The methodology involves deploying Moodle in parallel on VM and LXC environments with identical hardware specifications, followed by load simulation using scenarios that reflect real examination conditions such as mass login, question navigation, and simultaneous submission. The results indicate that LXC provides higher efficiency, demonstrating lower resource consumption and faster response times compared to VM. However, VM maintains advantages in system isolation, compatibility with low-level configurations, and stability when running complex or highly customized services. Based on these findings, Proxmox VE using LXC can be considered a suitable deployment choice for high-performance Moodle CBT environments where resource efficiency and responsiveness are prioritized, while VM remains beneficial for cases requiring strict isolation, enhanced configurability, or support for legacy components. These insights are expected to support educational institutions and system administrators in selecting an effective virtualization architecture for reliable, scalable, and performance-driven computer-based examination ecosystems.